Peningkatan Pengetahuan Lansia tentang Self-Management dalam Pengendalian Hipertensi melalui Pendidikan Kesehatan - Ayu, Windri Dewi; Jaelani, Ahmad; Yusup, Rian Maulana; Nugraha, Yophi; Yulianto, Pratama; Wati, Eti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Hypertension is one of the most prevalent non-communicable diseases among older adults, and low health literacy often becomes a major barrier to effective self-management. Health education plays an important role in improving the knowledge and ability of older adults to control blood pressure and prevent complications.  Objective: This activity aimed to evaluate the effectiveness of health education in improving hypertension self-management knowledge among older adults in Babakan Anyar Village, Kadipaten.  Methods: A pre-experimental one-group pre-test–post-test design was used, involving 32 older adults with hypertension identified through screening. The intervention consisted of a 60-minute educational session delivered through interactive lectures, discussions, and visual media covering low-salt diets, physical activity, medication adherence, blood pressure monitoring, and warning signs of hypertension. Knowledge was measured using a questionnaire before and after the session.  Results: Findings showed a significant improvement in knowledge levels, with participants categorized as having good knowledge increasing from 31% at pre-test to 78% at post-test. Wilcoxon analysis indicated a statistically significant difference between pre-test and post-test scores (z = –4.064; p < .001).  Conclusion: These results demonstrate that structured health education is effective in enhancing older adults’ knowledge regarding hypertension self-management. Similar programs are recommended to be implemented regularly as part of community-based efforts to empower older adults and improve hypertension control.